Effectiveness of Puppet Play Technique in Supporting Trauma Recovery for Child Victims of Sexual Abuse: A Case Study at Wijaya Kusuma Orphanage - sheila maulidina; Nurmawati (INSIGHT: Jurnal Bimbingan Konseling, 2025)
Child sexual abuse is a form of violence that has serious impacts on children’s psychological, emotional, and social conditions. Victims often experience trauma characterized by excessive fear, withdrawal, and difficulties is forming social interactions. Due to children’s limited verbal abilities, a non-verbal of which this doll play technique. This study aims to examine the effectiveness of the doll play technique in supporting trauma recovery for a child victim of sexual at Wijaya Kusuma Orphanage. The research employed a qualitative approach with Single-Subject Research (SSR) A-B-A design, consisting of three phases: initial baseline (A1), intervention using the doll play technique (B), and final baseline (B2). The focus of the study includes: 1) the dynamics of behavioral and emotional expression changes during the intervention, and 2) the role of symbolic representation through doll in the trauma recovery process. Data were collected through three primary methods: 1) participatory observation over eight sessions, 2) in-depth interviews with orphanage caregivers, and 3) a modified version of The Trauma Symptom Checklist of Children (TSCC) adjusted for a seven-year-old child’s comprehension level. Data were analyzed descriptively and qualitatively using source and method triangulation. The results showed a decrease in trauma symptom scores from the moderate to minimal category, as well as improvements in emotional expression and social engagement. The doll play technique proved to be an effective, empathetic, and relevant symbolic medium in assisting children’s trauma recovery in a non-clinical context.